Controlled trials of immunosuppressive therapy in hepatitis. Issue 584 (June 1974) - Stern, R. B.; Williams, Roger
Abstract : Three types of hepatitis are seen in children—acute viral hepatitis, active chronic hepatitis and the neonatal hepatitis syndrome. Few adequate controlled clinical trials of immunosuppressive therapy have been performed in these conditions, and none specifically in children. Many trials in the 1950s using corticosteroids were performed in acute viral hepatitis. Some showed that steroids were superior to controls and some showed no difference. Later trials confirmed that steroids were of no benefit in uncomplicated viral hepatitis, and further trials are now unjustifiable. Active chronic hepatitis is seen in all age groups, and there is little clear-cut evidence that the disease differs significantly in children from adults. Three well controlled clinical trials using immunosuppressive agents have been performed in this condition, but all were predominantly in adults. The conclusions were that steroids are the treatment of choice, although azathioprine may have a steroid-sparing effect. No prospective controlled trials of immunosuppressives have been carried out in the neonatal hepatitis syndrome, and in view of the variable prognosis there is an urgent need for one to be carried out. Large numbers, and a long follow-up period would be necessary and the trial need not be performed doubleblind.